2008
DOI: 10.1029/2008gl035127
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal subduction and truncation of the Cocos Plate beneath central Mexico

Abstract: Based on analysis of data from a trans‐Mexico temporary broadband seismic network centered on Mexico City, we report that the subducting Cocos Plate beneath central Mexico is horizontal, and tectonically underplates the base of the crust for a distance of 250 km from the trench. It is decoupled from the crust by a very thin low viscosity zone. The plate plunges into the mantle near Mexico City but is truncated at a depth of 500 km, probably due to an E‐W propagating tear in the Cocos slab. Unlike the shallow s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
306
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 261 publications
(321 citation statements)
references
References 21 publications
14
306
0
1
Order By: Relevance
“…Recent geophysical observations in central Mexico from dense seismic and GPS network data show that: 1) the plate interface dip shallows to nearly horizontal 150-300 km from the trench at a depth of ∼45 km ( Fig. 7b; Kim et al, 2010Kim et al, , 2012Perez-Campos et al, 2008); and 2) from the geodetic data there is almost no tectonic or interseismic coupling between the two plates along the flat slab portion (Larson et al, 2004).…”
Section: Central Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Recent geophysical observations in central Mexico from dense seismic and GPS network data show that: 1) the plate interface dip shallows to nearly horizontal 150-300 km from the trench at a depth of ∼45 km ( Fig. 7b; Kim et al, 2010Kim et al, , 2012Perez-Campos et al, 2008); and 2) from the geodetic data there is almost no tectonic or interseismic coupling between the two plates along the flat slab portion (Larson et al, 2004).…”
Section: Central Mexicomentioning
confidence: 99%
“…The low Vs layer (denoted as "ultra-slow velocity layer" (USL) by Song et al, 2009) atop the subducted Cocos crust appears to be in direct contact with overlying continental crust material (Kim et al, 2010(Kim et al, , 2012Perez-Campos et al, 2008), and the seismic velocity variations along the plate interface outline the seaward (updip) and landward (downdip) limits of the seismogenic zone (Song and Kim, 2012). The updip region near the Pacific coast shows a smaller…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Another feature of the Mexican subduction zone is the presence of a thin, low-velocity layer (LVL) observed above the entire length of the horizontal segment of the subducted plate (Pérez-Campos et al 2008). This layer extends parallel to the trench up to where the Cocos plate changes its geometry, to a dip of 41 • to the north (Dougherty et al 2012) and to a dip of 26 • (Melgar & Pérez-Campos 2011) to the south (Dougherty & Clayton 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1). Pérez-Campos et al (2008) showed that the subducting Cocos plate beneath central Mexico is flat, and lies just below the base of the continental crust over a distance of 250 km from the coast before plunging steeply into the mantle just south of Mexico City.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation